Construction of Ideology, Discursive Practices, and Power Relations in the Text of Kapatu Mbojo (Pantun Bima) as a Representation of Bima Culture - Sandi Rahmawati; Anwar Efendi (UIN Raden Mas Said Surakarta, Indonesia, 2026)
This research aims to uncover and analyze the relationship between ideology, discursive practices, and the use of language styles in Kapatu Mbojo (Pantun Bima) as a form of cultural representation of the Bima community. As an oral tradition rich in values, Bima Pantun is not merely a product of linguistic aesthetics, but a space for the contestation of meaning and a reflection of dynamic social structures. This study employs a qualitative approach using the framework of Critical Discourse Analysis (CDA) based on Norman Fairclough's three-dimensional model, integrating textual (micro), discursive practice (meso), and socio-cultural practice (macro) dimensions of analysis. Data were drawn from the book